Combined effects of ambient air pollution and home environmental factors on low birth weight. (February 2020) - Lu, Chan; Zhang, Weishe; Zheng, Xiangrong; Sun, Jingchi; Chen, Lv; Deng, Qihong
Abstract: Background: Low birth weight (LBW) remains a major public health problem worldwide, yet its crucial environmental risk factors are still unclear. Objective: To examine the association between LBW (term and preterm LBW) and prenatal exposure to ambient air pollution and home environmental factors as well as their combination, in order to identify critical time window for exposure and key outdoor and indoor factors in LBW development. Methods: A cohort study of 3509 preschool children was performed in Changsha, China during the period 2011–2012. A questionnaire was conducted to survey each child's birth outcome and each mother's exposure to home environmental factors including parental smoking, new furniture, redecoration, mold/damp stains, window pane condensation, and household pets during pregnancy. Maternal exposure to inhalable particulate matter (PM10 ), industrial air pollutant (SO2 ), and traffic air pollutant (NO2 ) was estimated during different time windows of gestation, including conception month, three trimesters, birth month, and whole gestation. Associations of term and preterm LBW with ambient air pollutants and home environmental factors were assessed by multiple logistic regression models in terms of odds ratio (OR) with 95% confidence interval (CI). Results: Term LBW (TLBW) was significantly associated with exposure to ambient PM10 during pregnancy, with OR (95% CI) = 1.47 (1.00–2.14) for per IQR increase after adjustment for the covariates and home environmental factors. Specifically, we identified the significant association in early phase of pregnancy including conception month (1.90, 1.09–3.30) and the first trimester (1.72, 1.10–2.69). We further found that TLBW was significantly related with parental smoking at home, OR (95% CI) = 2.17 (1.09–4.33). However, no association was observed for preterm LBW (PLBW). The TLBW risk of ambient air pollution and home environmental factors was independent each other and hence the combined exposure to ambient PM10 and indoor parental smoking caused the highest risk. Sensitivity analysis suggested that foetus with younger mothers were significantly more susceptible to risk of indoor parental smoking, while those with smaller house and cockroaches were more sensitive to risk of outdoor PM10 exposure. Conclusion: Prenatal exposure to combined outdoor and indoor air pollution, particularly in critical window(s) during early pregnancy, significantly increases the risk of term LBW. Highlights: Air pollution was associated with term low birth weight (LBW) but not with preterm LBW. We found term LBW was associated with prenatal exposure to ambient inhalable particle (PM10 ). Term LBW was also related with parental smoking at home during pregnancy. Exposure to combined outdoor and indoor air pollution posed the highest risk of term LBW. Early pregnancy was identified as the most critical time window for exposure susceptibility.